Safety Does Not Happen by Accident: Antecedents To A Safer Warehouse. Issue 8 (28th February 2016) - de Vries, Jelle; de Koster, René; Stam, Daan
Abstract : On a daily basis, thousands of employees suffer from severe occupational accidents worldwide. These accidents not only lead to negative consequences for the physical and mental health of employees, but also to high costs for companies and the society as a whole. A large share of these accidents take place in warehouses. Prior research has demonstrated the critical role of leadership, and especially safety‐specific transformational leadership (SSTL), in reducing warehouse accidents. Yet several important questions concerning SSTL remain: What effects does SSTL have on outcomes other than safety, and what determines whether leaders display SSTL behaviors? To answer these questions, this research studies the relationship between SSTL of warehouse managers and not only occupational accidents, but also quality and productivity. Moreover, it investigates the managers who are most likely to display SSTL. Data from 87 warehouse managers and 1233 employees were used to test the conceptual model. The results suggest that the dispositional prevention focus of the manager (one of two possible motivational strategies that people deploy) positively relates to SSTL, and that SSTL negatively relates to occupational accidents. Furthermore, SSTL and its identified negative relationship with occupational accidents does not appear to have detrimental impact on productivity or quality. These results extend existing models of SSTL and safety, and can help companies to reduce the number of accidents and the associated costs by selecting and developing safety‐specific transformational leaders.